Pengaruh manajemen waktu dan motivasi belajar terhadap prestasi akademik mahasiswa politeknik muara teweh - Maslianor (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This research was conducted with the aim of: (1). Testing and analyzing the partial influence of time management on academic achievement of Muara Teweh Polytechnic students. (2). Testing and analyzing the partial influence of learning motivation on academic achievement of Muara Teweh Polytechnic students. and (3). Testing and analyzing the influence of time management and learning motivation simultaneously on academic achievement of Muara Teweh Polytechnic students. This research uses explanatory research. While the data sources use primary data through questionnaires and secondary data. The population in this study are students who are still actively studying at Muara Teweh Polytechnic. The sample in this study is 70 Muara Teweh Polytechnic students with a sampling technique using saturated sampling. Data collection techniques are by means of observation, questionnaires, literature, and documents. Data validity testing is carried out by validation testing and reliability testing. The data analysis technique uses the IBM SPSS Statistics Program Version 25, the analysis method used is multiple linear regression analysis. The results of the study indicate that Time Management partially has a statistically significant but negative effect on Student Academic Achievement and Learning Motivation partially has a significant and positive effect on Student Academic Achievement. Meanwhile, Time Management and Learning Motivation simultaneously have a significant effect on Student Academic Achievement at Muara Teweh Polytechnic.